Endoscopic Endonasal Transsphenoidal Approach in the Management of Sellar and Parasellar Lesions - Ligia Tataranu; M. R. Gorgan; V. Ciubotaru; Adriana Dediu; B. Ene; D. Paunescu; Anica Dricu; V. Pruna (Romanian Neurosurgery, 2010)
Transsphenoidal approaches have been used for a century for the resection of pituitary and other sellar tumors. In the past decade, however, the endoscopic endonasal transsphenoidal approach has been proposed as a minimally invasive procedure for the treatment of pathologies of the sellar region. This procedure introduces various advantages compared with the transsphenoidal microsurgical approach, such as an improved vision of the surgical field, less traumatism of the nasal structures and reduced complications. Patients’ quick recovery, short hospital stays and minimal postoperative discomfort have been observed. More recently, the standard endoscopic endonasal technique has been extended to provide access to parasellar lesions. This expansion carries significant potential for the resection of skull base lesions. In this article, the authors review the indications of the endoscopic endonasal transsphenoidal approach and define the main phases of the standard surgical technique. Preoperative evaluation, equipment, preoperative and postoperative care are presented. Endoscopic endonasal technique is a safe and effective method for removal of most sellar and some parasellar masses, providing more complete lesion excision and reducing complications.